Effects of the flavonol quercetin and α-linolenic acid on n-3 PUFA status in metabolically healthy men and women: a randomised, double-blinded, placebo-controlled, crossover trial. Issue 5 (3rd April 2017) - Burak, Constanze; Wolffram, Siegfried; Zur, Berndt; Langguth, Peter; Fimmers, Rolf; Alteheld, Birgit; Stehle, Peter; Egert, Sarah
Abstract: Increased dietary intake and tissue status of the long-chain n -3 PUFA, EPA and DHA, is associated with cardiovascular benefits. Epidemiological and animal studies suggest that concomitant nutritive intake of flavonoids may increase the conversion of α -linolenic acid (ALA) to longer-chain n -3 fatty acids EPA and DHA. We investigated the effects of increased ALA intake on fatty acid composition of serum phospholipids and erythrocytes in metabolically healthy men and women and whether fatty acid profiles and ALA conversion were affected by regular quercetin intake or sex. Subjects ( n 74) were randomised to receive at least 3·3 g/d ALA with either 190 mg/d quercetin (ALA+quercetin) or placebo (ALA+placebo) in a double-blinded, placebo-controlled, crossover trial with 8-week intervention periods separated by an 8-week washout period. A total of seven subjects dropped out for personal reasons. Data from the remaining sixty-seven subjects (thirty-four males and thirty-three females) were included in the analysis. Both interventions significantly increased serum phospholipid ALA (ALA+placebo: +69·3 %; ALA+quercetin: +55·8 %) and EPA (ALA+placebo: +37·3 %; ALA+quercetin: +25·5 %). ALA + quercetin slightly decreased DHA concentration by 9·3 %. Erythrocyte ALA and EPA significantly increased with both interventions, whereas DHA decreased. Fatty acid composition did not differ between sexes. We found no effect of quercetin. Intake of 3·6 g/d ALA over an 8-week period resulted in increased ALA and EPA, but not DHA, in serum phospholipids and erythrocytes. Neither quercetin supplementation nor sex affected the increment of ALA and relative proportions of n -3 PUFA in serum phospholipids and erythrocytes.